Improving urban non-motorized mobility for public affairs trips: A survey and analysis of innovative official bicycles in Nanjing city, China - Fei Shi (Journal of Urban Management, 2019)
Mobility and accessibility are two important factors of urban transportation planning and design. Generally, mobility is described as the right and convenience of using different modes of transport. We usually focus on commuting mobility, business mobility, and the mobility of vulnerable groups, but tend to ignore the mobility of public affairs, which is also an extremely important consideration. Official Bicycles have become an issue of vital importance due to public concern about green travel, reform of the official business-car system and reduction of public expenditures. In order to explore the feasibility of this new traffic tool for official business, a survey was conducted on the Official Bicycles of Government of Gulou District in Nanjing by means of questionnaires and interviews of both officials and citizens, as well as follow-up and simulation surveys of official travel behavior. On this basis, comparisons between Official Bicycles and official cars were made in terms of efficiency, cost and carbon emissions. The results substantiate the feasibility and rationality of Official Bicycles as well as identify some problems. In order to promote feasible and reasonable bicycle transportation and maximize its advantages, suggestions are proposed from the perspectives of changing public policy, urban planning optimization and social values.
Keywords: 710; Urban mobility; Official bicycles; Reform of official-business-car-using system; External cost